Development of patient-centred standards of care for osteoarthritis in Europe: the eumusc.net-project. Issue 6 (21st November 2014) - Stoffer, Michaela A; Smolen, Josef S; Woolf, Anthony; Ambrozic, Ales; Berghea, Florian; Boonen, Annelies; Bosworth, Ailsa; Carmona, Loreto; Dougados, Maxime; de Wit, Maarten; Erwin, Josephine; Fialka-Moser, Veronika; et al.
Abstract : Objective: The eumusc.net project is an initiative founded by the European Community and the European League Against Rheumatism. One aim of the project was to facilitate equal standards for musculoskeletal health across Europe. The aim of this work-package was to develop patient-centred and consensus based standards of care (SOC) for osteoarthritis (OA), which should be available in a professional and a patient version. Methods: A systematic review concerning guidelines dealing with OA was conducted. Furthermore, experts in musculoskeletal diseases were contacted to ensure that 'grey' literature was not excluded. Documents that fulfilled predefined inclusion/exclusion criteria were included and all interventions for OA were extracted and categorised. Based on this list of interventions, a three round Delphi exercise with an international and multidisciplinary expert panel, including patient research partners, was performed to achieve expert consensus. Results: Six documents were included and used for further analysis. Out of them, 46 interventions have been extracted and 10 consensus based SOC were formulated. In addition, a patient version, written in a lay-understandable wording and in the format of checklist questions was developed. An example is SOC 5: "People with OA should achieve optimal pain control using pharmacological and non-pharmacological means." The matching patient-centred checklist question reads: "Do I know how to control pain associated with OA?" Conclusions: The SOC for OA will be available in the 23 languages of the European Union to enhance unified information to patients and professionals and to further harmonise the treatment/care of OA within Europe.